Human capital investment and globalization in extortionary states; Humankapitalinvestitionen und Globalisierung in Ausbeutungsstaaten - Fredrik Andersson; Kai A. Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
This paper considers education investment and public education policy in closed and open economies with an extortionary government. The extortionary government in a closed economy chooses an education policy in order to overcome a hold-up problem of time-consistent taxation similar to benevolent governments. The two types of government differ in their education policies if highly productive labor is mobile. Extortionary governments. incentives for a policy that stimulates higher private education efforts vanish; instead they have incentives to prevent individuals from mobility-increasing education investment. Tax competition therefore reduces hold-up problems of time-consistent extortionary taxation, but introduces other distortions that reduce workers. utility. – – In der Arbeit untersuchen wir private und öffentliche Humankapitalinvestitionsentscheidungen in geschlossenen und offenen Volkswirtschaften. Wir unterstellen für die Analyse eine stark eigennutzorientierte Regierung, die versucht, die Nettosteuereinnahmen zu maximieren und diese Einnahmen für Zwecke verausgabt, die nicht den Nutzen der Staatsbürger mehren. Es zeigt sich, dass auch eine solche Regierung in einer geschlossenen Volkswirtschaft öffentliche Bildungsinvestitionen tätigt bzw. private Bildungsinvestitionen subventioniert, weil sie damit ein Problem mangelnder staatlicher Selbstbindung löst. Wir betrachten dann offene Volkswirtschaften, in denen die gutausgebildeten und produktiven Individuen international mobil sind. In der resultierenden Steuerwettbewerbssituation verzichten eigennutzorientierte Regierungen auf öffentliche Bildungsinvestitionen und Bildungssubventionen und versuchen unter Umständen sogar, private Bildungsinvestitionen zu behindern.
Keywords: H21; H23; 330; Migration; education; globalization; commitment; time consistent income taxation